13-Acetoxysarcocrassolide induces apoptosis in human hepatocellular carcinoma cells through mitochondrial dysfunction and suppression of the PI3K/AKT/mTOR/p70S6K signalling pathway. (31st December 2022) - Hsu, Chang-Min; Lin, Jen-Jie; Su, Jui-Hsin; Liu, Chih-I
Abstract: Context: 13-Acetoxysarcocrasside, isolated from the Taiwanese soft coral Sarcophyton crassocaule Moser (Alcyoniidae), has biological activity and induces apoptosis in hepatocellular carcinoma cells. Objective: To elucidate the mechanisms underlying apoptosis induced by 13-acetoxysarcocrasside in HA22T and HepG2 hepatocellular carcinoma cells. Material and methods: MTT and morphology assays were employed to assess the anti-proliferative effects of 13-acetoxysarcocrasside (1–5 μM). TUNEL/DAPI staining and annexin V-fluorescein isothiocyanate/propidium iodide staining were used to detect apoptosis. Cells were treated with13-acetoxysarcocrassolide (0, 1, 2, and 4 μM) for 24 h, and the mechanism of cells apoptotic was detected by western blotting. Cells treated with DMSO were the control. Results: Survival of the cells decreased with the addition of 13-acetoxysarcocrassolide, and at 4 μM cell survival was inhibited by approximately 40%. After treatment of cells with 13-acetoxysarcocrassolide, the incidence of early/late apoptosis to be 0.3%/0.5%∼5.4%/22.7% for HA22T cells, in the HePG2 cells were 0.6%/0.2%∼14.4%/23.7%. Western blotting analysis showed that the expression of Bax, Bad, cleaved caspase 3, cleaved caspase 9, cleaved-PARP-1, cytochrome c, and p -4EBP1 increased with an increasing concentration of 13-acetoxysarcocrasside (0, 1, 2, and 4 μM), whereas that of Bcl-2, Bcl-xL, Mcl-1, p -Bad, p -PI3K, p -AKT, p -mTOR, p -70S6K, p -S6, p -eIF4E, and p -eIF4B decreased. Discussion and conclusions: Apoptosis induced by 13-acetoxysarcocrassolide in HA22T and HepG2 cells is mediated by mitochondrial dysfunction and inactivation of the PI3K/AKT/mTOR/ p 70S6K pathway. The potential of 13-acetoxysarcocrassolide as a chemotherapeutic agent should be further assessed for use in human hepatocellular carcinoma treatment.